2022
DOI: 10.1177/10664807221104133
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Therapeutic Effectiveness of Genograms in Family Therapy: A Literature Review

Abstract: The primary aim of the literature review is to explore the relevant literature on the use and effectiveness of genograms in family therapy. The literature is predominantly related to the use of genograms in various settings and adaptations. There are minimal studies on the effectiveness of genograms as a therapeutic tool in family therapy. Searches were conducted of MEDLINE, EMBASE, CINAHL, SCOPUS and PsycINFO electronic databases. The international review includes all studies, irrespective of study methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…The work of social educators with both the child and their family sets the groundwork for the successful overcoming of psychological trauma consequences. Joseph, Dickenson, McCall & Roga, (2023) indicated that the better results are achieved when the entire family is involved in the therapeutic process.…”
Section: Research Resultsmentioning
confidence: 99%
“…The work of social educators with both the child and their family sets the groundwork for the successful overcoming of psychological trauma consequences. Joseph, Dickenson, McCall & Roga, (2023) indicated that the better results are achieved when the entire family is involved in the therapeutic process.…”
Section: Research Resultsmentioning
confidence: 99%
“…Therapists can establish a welcoming atmosphere by incorporating elements of cultural sensitivity into their practice, such as displaying cultural artifacts or decorations in the therapy room, offering materials in multiple languages, and actively seeking input from clients regarding their cultural preferences and traditions (Kreshak, 2020;. In English-language family therapy, it is essential to validate the experiences of all family members, regardless of their cultural background (Joseph et al, 2023). This involves actively listening to and empathizing with each individual's perspective, acknowledging the impact of cultural influences on their beliefs and behaviors.…”
Section: Opportunities For Positive Engagementmentioning
confidence: 99%
“…For instance, genograms may not be the best assessment tool for high‐conflict couples who tend to engage in more “heated” communications in the beginning stage of therapy (Finney & Tadros, 2018), or if a client went through the foster care system or was adopted and who may not have a lot of context about their family heritage. Further, the effectiveness of genograms is significantly associated with therapist training and cultural competency (Joseph et al, 2023). Finally, although genograms provide a pictorial image for clients, the relationships are often shown as flat and linear.…”
Section: Existing Toolsmentioning
confidence: 99%